Assessing Lecturers’ Acceptance towards Online Learning System: The Institutional Theory Perspective - Kusuma, Anggraini Candra; Basori, Basori; Budiyanto, Cucuk Wawan (Universitas Sebelas Maret, 2020)
This research aims to assess the lecturers’ acceptance level in using the Online Learning System (SPADA). The institutional theory is an extension of the Technology Acceptance Model (TAM), which is it analyzed variables of perceived usefulness, perceived ease of use, coercive pressure, normative pressure, mimetic pressure and behavior intention. This research used quantitative research design with survey method. Meanwhile, the sampling technique used cluster random sampling. The respondents of this research were lecturers who had applied SPADA at a state university in Central Java. In this research, the assessment of the questionnaire used the Likert scale. Besides, the tests used instrument test, classic assumption test, multiple regression analysis, and hypothesis testing by using SPSS. The result shows that from the six hypotheses that had been tested, the hypotheses of H1, H2, H3, H4 have no significant influence and the hypotheses of H5 and H6 have significant influence. It means the lecturers who have high social status are influencing others lecturers who have low social status in adopting SPADA although all variables have contribution in influencing the lecturers on behavior intention to adopt SPADA. It indicates the social factor is being attention in analyzing behavior intention in adopting technology.